Performance, health and physiological responses of newly weaned feedlot cattle supplemented with feed-grade antibiotics or alternative feed ingredients. (26th March 2018) - de Souza, K. A.; Cooke, R. F.; Schubach, K. M.; Brandão, A. P.; Schumaher, T. F.; Prado, I. N.; Marques, R. S.; Bohnert, D. W.
Abstract : With increased regulations regarding the use of feed-grade antimicrobials in livestock systems, alternative strategies to enhance growth and immunity of feedlot cattle are warranted. Hence, this experiment compared performance, health and physiological responses of cattle supplemented with feed-grade antibiotics or alternative feed ingredients during the initial 60 days in the feedlot. Angus×Hereford calves (63 steers+42 heifers) originating from two cow–calf ranches were weaned on day −3, obtained from an auction yard on day −2 and road-transported (800 km; 12 h) to the feedlot. Upon arrival on day −1, shrunk BW was recorded. On day 0, calves were ranked by sex, source and shrunk BW, and allocated to one of 21 pens. Pens were assigned to receive (7 pens/treatment) a free-choice total mixed ration containing: (1) lasalocid (360 mg/calf daily of Bovatec; Zoetis, Florham Park, NJ, USA)+chlortetracycline (350 mg/calf of Aureomycin at cycles of 5-day inclusion and 2-day removal from diet; Zoetis) from days 0 to 32, and monensin only (360 mg/calf daily of Rumensin; Elanco Animal Health, Greenfield, IN, USA) from days 33 to 60 (PC), (2) sodium saccharin-based sweetener (Sucram at 0.04 g/kg of diet dry matter; Pancosma SA; Geneva, Switzerland)+plant extracts containing eugenol, cinnamaldehyde and capsicum (800 mg/calf daily of XTRACT Ruminants 7065; Pancosma SA) from days 0 to 32 and XTRACT only (800 mg/calf daily) from days 33 to 60 (EG) or (3) no supplemental ingredients (CON; days 0 to 60). Calves were assessed for bovine respiratory disease (BRD) signs and dry matter intake was recorded from each pen daily. Calves were vaccinated against BRD pathogens on days 0 and 22. Shrunk BW was recorded on day 61, and blood samples collected on days 0, 6, 11, 22, 33, 43 and 60. Calf ADG was greater ( P =0.04) in PC v . EG and tended ( P =0.09) to be greater in PC v . CON. Feed efficiency also tended ( P =0.09) to be greater in PC v . CON, although main treatment effect for this response was not significant ( P =0.23). Mean serum titers against bovine respiratory syncytial virus were greater in EG v . PC ( P =0.04) and CON (tendency; P =0.08). Collectively, the inclusion of alternative feed ingredients prevented the decrease in feed efficiency when chlortetracycline and ionophores were not added to the initial feedlot diet, and improved antibody response to vaccination against the bovine respiratory syncytial virus in newly weaned cattle.